How to use new transrectal ultrasound in prostate cancer detection and biopsy for beginners and experts - Byung Kwan Park (Precision and Future Medicine)
Many radiologists and urologists believe that many prostate cancers are invisible under transrectal ultrasound (TRUS) imaging. Frequently, they use TRUS only as a guiding tool or fuse TRUS images with magnetic resonance images for prostate biopsy in men with high prostate specific antigen. However, TRUS software and hardware have been developed and have potential to depict many prostate cancers. Currently, there are only a few papers dealing with how to use TRUS for detection and biopsy of prostate cancers. The aim of this review is to describe the new TRUS techniques, imaging features, and biopsy techniques.